The Influence of Business Risk and Company Size on Capital Structure in Industrial Sector Companies Listed on the Indonesian Stock Exchange - Tanti Septiani BR Sembiring; Riska Franita; An Suci Azzahra (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The goal of this study is to investigate the impact that business risk and company size have on the capital structure of industrial businesses that are listed on the Indonesia Stock Exchange between the years 2021 and 2024 on the Indonesia Stock Exchange. For the purpose of capital structure, the Basic Earnings Power Ratio (BEPR) is used to assess risk, the Natural Logarithm (LN) is used to assess the size of the organization, and the Debt to Equity Ratio (DER) is used to do capital structure analysis. In this particular study, a quantitative approach was taken, and the statistical software that was utilized for the analysis was SPSS version 27. The research objectives were met by 27 different companies, and samples obtained were from them through the use of purposeful sampling. Compared to 0.05, the significant value of the t-test, which is 0.301, is higher. The t-table value of 1.98282 is exceeded by the estimated value of -1.038, which is lower than the t-table value. It may be derived from this that the capital structure is not significantly impacted by the risk that the business faces. Nevertheless, this does not apply to the size of the company. This is demonstrated by a significance value of 0.001 and a calculated t-value of 3.319, both of which are higher than the value of 1.98282 that is seen in the t-table statistic. Meanwhile, the capital structure of a firm is positively and significantly impacted by both the growth of the organization and the risks that it faces. There is a significant difference between the F-value of 5.685 and the F-table value of 3.08, with the sig. value being 0.005. According to the adjusted R-Square value of 0.081, the variance in capital structure may be explained by business risk and firm size to the extent of up to 8.1% of the total variation. On the other hand, 91.9% of this variation consisted of additional factors that were not investigated.